Lecturers’ Method of Teaching Mathematics: Engineering Technology Students’ Perceptions in UTeM - Hamzah, Khairum; Waini, Iskandar; Salim, Fadzilah; Kashi'ie, Najiyah Safwa; Zainal, Nurul Amira; Mohd Said, Rahaini (2014)
Teaching Mathematics courses at the tertiary level institutions nowadays can be quite challenging especially when the delivery method for the subject matter is known to always be very traditional using the chalk and board. This study examined the Engineering Technology (ET) students’ perceptions of their lecturers’ teaching method for Mathematics courses at the Faculty of Engineering Technology (FTK), Universiti Teknikal Malaysia Melaka, Malaysia (UTeM). A mini survey with quantitative research methods was utilized. 264 second year ET students with different fields of studies at FTK, UTeM, were asked to complete a set of questionnaires administered during the final week of the semester. A questionnaire consists of questions regarding how students perceive their lecturers’ teaching method during the class sessions. From the findings, conclusion has been drawn regarding the students’ perceptions of their Mathematics lecturers in promoting different methods in teaching Mathematics. The result shows that most of the mathematics lecturers incorporated both active and passive teaching methods in teaching of the subject matter.